2018
DOI: 10.1038/s41598-018-27588-7
|View full text |Cite
|
Sign up to set email alerts
|

The strategies and outcomes of left subclavian artery revascularization during thoracic endovascular repair for type B aortic dissection

Abstract: This study was to analyze the outcomes of left subclavian artery (LSA) revascularization during thoracic endovascular repair (TEVAR) for type B aortic dissections (TBAD). From 2011 to 2017, TBAD patients who underwent LSA revascularization during TEVAR were enrolled. Technical success, endoleaks, mortality, complication, reintervention, and patency of target vessels were analyzed. 38 patients were included, 14 underwent carotid-subclavian bypass (CSB), and 24 underwent chimney graft (CG) implantation. Technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
5
19
0
2
Order By: Relevance
“…6) In fact, there are only four studies exclusively comparing carotid-subclavian bypasses or subclavian-carotid transposition to chimney or periscope-sandwich grafts for LSA debranching. 8,[15][16][17] Table 4 demonstrates their results along with studies that examined either open or parallel graft-based LSA debranching only. 2,4,6,9,18) A former study from the reporting institution also described results of periscope-sandwich grafts for LSA debranching, but as only some of the patients were included into the presented cohort, their results were not used for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6) In fact, there are only four studies exclusively comparing carotid-subclavian bypasses or subclavian-carotid transposition to chimney or periscope-sandwich grafts for LSA debranching. 8,[15][16][17] Table 4 demonstrates their results along with studies that examined either open or parallel graft-based LSA debranching only. 2,4,6,9,18) A former study from the reporting institution also described results of periscope-sandwich grafts for LSA debranching, but as only some of the patients were included into the presented cohort, their results were not used for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, statistical differences were neither detected for strokes, mortality, or reintervention rate. 8,[15][16][17] Nevertheless, all comparative studies reported more aortic reinterventions after parallel grafts than after open procedures. 8,[15][16][17] Our rate of 33% for parallel grafts is in line with Johnson et al, but others have reported much lower rates of 0.6%-12.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…de manera ordinaria o electiva, siempre y cuando no se encuentre alguna contraindicaci贸n absoluta para no realizarlo, lo cual no se present贸 en ning煤n paciente 6,7 . El seguimiento cl铆nico despu茅s de la exclusi贸n del ostium de la subclavia es estrecho, ah铆 se valora continuamente la presencia de claudicaci贸n, lesiones isqu茅micas o s铆ndrome de robo subclavio y, en caso necesario, se realiza una revascularizaci贸n, sin embargo, no ha sido necesario en ninguno de los pacientes de esta serie.…”
Section: B Aunclassified
“…Dentro de la literatura, encontramos estudios donde se busca la preservaci贸n del flujo en la arteria subclavia 7,8 , e igualmente comparaci贸n entre la realizaci贸n de bypass car贸tido-subclavio vs. manejo endovascular, sin encontrar diferencias significativas 9 , sin embargo, no hay mucha evidencia en el manejo con chimeneas del resto de los vasos supraa贸rticos 5,[10][11][12] . En la poca evidencia encontrada se observa que el manejo de zonas de anclaje m谩s proximales se reserva a patolog铆a del arco a贸rtico y aorta ascendente 5,11,13,14 .…”
Section: Introductionunclassified